Beliefs of primary and secondary teachers about the assessment of French foreign language - Chao Chao, Kuok Wa (2022)
In Costa Rica, French as a foreign language is taught in some primary schools and it is an obligatory class in secondary education. However, the issue of teachers' beliefs in assessment has not been much researched in the country. Therefore, the objective of this research is to describe the beliefs of French teachers as a foreign language concerning assessment. This is quantitative descriptive research conducted in Costa Rica. A questionnaire with open and closed questions applied online was used for data collection in the first semester of 2020 and there were 84 teachers who submitted their answers, representing 10% of French teachers in Costa Rica. For closed questions, the Likert scale was used. As conclusions and main results, it was found that there is an inclination of the teachers towards new practices in assessment such as the participation of students in their self-assessment, assessment as learning, the importance of solving complex problems in assessment, among others. However, some beliefs persist towards the traditional perspective such as the importance of the grade, teachers begin the main responsible for the entire assessment process. This aspect can offer an opportunity to continue with teacher training in order to generate a paradigm shift in assessment.